Strategi Kepala Madrasah dalam Program Ekstrakurikuler di MINU Nurul Huda Kecamatan Gempol Kabupaten Pasuruan - Asmunir Asmunir; Abu Darim (PEDIR: Journal of Elementary Education, 2022)
This study aims to find and describe the strategies used by Madrasah heads in developing a management system for Scout extracurricular activities at MINU Nurul Huda, Gempol District, Pasuruan Regency and to describe the development of a Scout extracurricular activity management system at MINU Nurul Huda, Gempol District, Pasuruan Regency. This study uses a qualitative approach with a qualitative descriptive method. While this type of research is field research (field research). The research data were collected using the methods of observation, interviews and documentation. The data collected from these techniques were analyzed using data reduction, data presentation and data verification, data validity was obtained using data triangulation. The results of this study indicate that the principal's strategy has used the principles of the management system. The principles in question are continuous and continuous improvement, focus on activities and total involvement. The indicators are related to continuous improvement including quality and competency improvements. Scout extracurricular activities are carried out in accordance with the management system from Planning, Organizing, Actuating and Controlling.